Analysis of Self-Quality Sharia Life Insurance Agents as Sharia Human Resources Competitiveness - Novi Indriyani Sitepu (Proceedings of AICS - Social Sciences, 2020)
Islamic Insurance agents as sharia human resources are the spearhead of the insurance industry. The improvement of the quality from sharia insurance agent which consist of: physical and health qualities, intellectual quality and spiritual quality must be maintained in order to have the ability to compete. Therefore, an analysis of the agent’s self-quality needs to be known more deeply to improve the competitiveness of human resources in order to be able to compete in the international arena. This study uses a qualitative method using Analysis Networking Process (ANP). Primary research data were obtained through interviews with agency branch leaders, Million Dollar Round Table (MDRT) and Indonesia Islamic Insurance Association (AASI), secondary data were obtained from literature studies. The result show that quality as a solution to increasing the competitiveness of Islamic insurance agents are: simultaneously there is an agreement among respondents regarding the priority order of Islamic insurance agents as much as 77 percent with the highest priority, it is spiritual quality; simultaneously there was an agreement among respondents regarding the priority order of alternative strategies for sharia insurance agents as much as 68 percent with the highest priority, it is training and education.